КРЕДИТ-МОДУЛЬ ТИЗИМИ – ТАЪЛИМ СИФАТИНИ ТАЪМИНЛАШ ОМИЛИ СИФАТИДА - Ғаниев, О.А. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of training personal meeting the reguirements of world standards in the process of reforms of higher education system. Some achievements reconized on a global scall in educational institutions ase given.
Keywords: Moodle education; competence; competence approach; didactic aim; content of education; ECTS; educational means; volume